Post-Pandemic Implementation of the School Literacy Movement (GLS) at Islamic Elementary School - Aliya Nur Alfi Nabila (IAIN Surakarta, 2023)
Since 2019, the corona outbreak has spread so that learning is online. The tasks the teacher gives do not fully help children learn but burden children and parents, hampering children's literacy habituation. This research is deemed necessary to determine the School Literacy Movement (GLS) implementation and the inhibiting and supporting factors of literacy. This research uses a descriptive qualitative method. The location in this study is MIN 4 Sukoharjo. Data collection techniques are interviews, documentation and observation. The research instruments included field note sheets, documentation, and interview sheets. The subjects of this study were deputy heads in the field of R&D, homeroom teachers, and grade 1 and grade 4 students. The results showed that implementing the School Literacy Movement at MIN 4 Sukoharjo was not optimal due to changes in offline-online-offline learning returning after the pandemic. Factors inhibiting the implementation of GLS at MIN 4 Sukoharjo are limited reading materials, some classes do not have reading corners, library transfers, parental economics and parenting. Factors supporting the implementation of GLS include: the availability of facilities, excellent programs, learning that is designed with various methods, and teachers can build good communication with parents.